The concept of reducing the man-made impact of launches of the promising Irtysh launch vehicle in the impact areas of the Baikonur cosmodrome - B. T. Suimenbayev; V. I. Trushlyakov; G. T. Yermoldina; Zh. B. Suimenbayeva; A. M. Bapyshev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Scientific and methodological approaches to minimizing the man-made impact of launches of promising carrier rockets of the «Irtysh» type by oxygen-kerosene main liquid-propellant rocket engines of the Baiterek rocket complex in areas of falling of the Baikonur cosmodrome are considered. The basic directions for reducing the anthropogenic impact of the spent booster of the first stage of the «Irtysh» type LV in the areas of falling are: determination of optimal areas for the spent booster to fall in selected areas of the FA with the highest stability and minimum cost of works on restoring the soil state — (A); controlled descent of the spent booster after separation from the LV to the designated section of the fall with an accuracy not exceeding the size of the selected optimal section — (B). To solve problems of direction A, it is proposed to create an additional information and analytical system of the area of falling. To solve the problems of direction B, possible design solutions are proposed based on the evaporation of non-producing liquid propellant residues in the spent booster tanks, and using the resulting vapor-gas mixtures for controlled descent of spent booster to the designated FA zone